Pengaruh Gratitude Training untuk Meningkatkan Subjective Well-Being pada Remaja Panti Asuhan Aisyiyah Bukittinggi - Mutiara Chikita; Nadira Rindiani Hutasushut; Tuti Rahmi (CV. ITTC INDONESIA, 2026)
Adolescents living in orphanages, given the circumstances and rules that apply there, certainly need to make an effort to achieve a high level of subjective well-being. This study aims to examine whether gratitude training has an effect on improving subjective well-being among adolescents in orphanages. It uses an experimental method with a pretest-posttest control group design. The subjects of this study were 10 adolescents from the Aisyiyah Bukittinggi orphanage, consisting of five participants in the experimental group and five participants in the control group. Based on the data analysis using the Mann-Whitney Test on the SWLS (Life Satisfaction Scale) section, the Asymp. sig. (2-tailed) was 0.047, where 0.047 < 0.05, meaning Ha was accepted and there was an effect of gratitude training on the life satisfaction component of subjective well-being among orphanage adolescents. For the SPANE scale (affective component), the Asymp. Sig. (two-tailed) was 0.671, meaning 0.671 > 0.05; thus, Ha was rejected, and there was no effect of gratitude training on the affective component of subjective well-being among orphanage adolescents. These findings indicate that gratitude training only affects the life satisfaction component of subjective well-being among orphanage adolescents, while it has no effect on the affective component. However, based on the gain score results, the effectiveness of this intervention could not yet be considered effective.